The Utilization of Islamic Comic Media in Enhancing Students’ Interest in Learning Islamic Cultural History (SKI): The Childhood of Prophet Muhammad - Rahma, Nafisa Aulia Nadia; Aulia, Maulidah; Yanti, Fika Elma; Zahrani, Syifa Falizia; Kumala, Sinta; Islami, Shava Aqoqoh Al; Fadlika, Aisyah; Rif’iyati, Dian (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Learning Islamic Cultural History (ISHC) in Islamic Elementary Schools (MI) currently still faces various obstacles, one of which is low student interest and memory due to monotonous lecture methods on the material, even though elementary school-aged students need concrete visual media to understand the material clearly. This study aims to identify the potential of using Islamic comics as a learning media tool to increase student interest and understanding in ISHC subjects. By using a literature study method (library research) through a qualitative descriptive approach, this study examines various scientific literature and relevant research results. The results of the study indicate that Islamic comic media is able to visualize complex historical narratives into simpler and more interesting, so it is more effective in increasing student active involvement and strengthening memory compared to conventional media. It can be concluded that the innovation of Islamic comic media is a strategic solution to overcome obstacles to learning ISHC because it is able to increase learning motivation that is in line with the characteristics of students' cognitive development.